(untitled) (Cadernos de Sociomuseologia, 2019)
The article presents a case study carried out by a direct participant in the gestation and management experience of the Football Museum in São Paulo, Brazil. It is also the presentation of existing opportunities in the interrelation between curation, museography and architecture at the service of the educational process. The text begins by pointing out the importance of football in the feeling of belonging of the Brazilians, an originally elitist sport that was appropriated and subverted by the popular sectors. Advances by presenting the structure of this "word museum" that seeks to tell the story of the twentieth century through the Brazilian national passion for this sport. It reviews the various rooms, features and services, from its physical structure to educational work, including the possibilities of interaction between the architectural project and the street and the Pacaembu stadium, a historical heritage. Keywords: Football Museum; History; Education; Architecture; Curation; Museology